Characterization and Molecular Identification of Vibrio cholerae from Sea Beach Using 16S rRNA Sequencing - Bhatta, Kalpita; Samal, Priyadarshani; Rout, Jyoti Ranjan; Sahoo, Santi Lata (Asian Journal of Biological and Life Sciences)
Background: Developed and developing countries were confronted with public health concerns due to the devastating contamination of deadly microbes. Vibrio is one among them which is associated with contaminated water resources and food materials. The disease cholera, a gastroenteric, has recorded a history of seven pandemics globally, but in much of Asia, Africa, and Latin America. The present investigation elucidates with characterization and molecular identification of Vibrio from contaminated water of the urban waste discharge point of the Puri Sea beach, Odisha, India as studies have shown that the Bay of Bengal has been the native for variants of Vibrio cholerae. Materials and Methods: The bacteria were isolated in nutrient agar and Thiosulfate Citrate Bile Salt (TCBS) agar medium with distinct cultural characteristics of Vibrio. 16S rRNA was identified DNA was isolated by centrifugation at 5000rpm for 10 min. Amplification of DNA was carried out and the 16 S rRNA was amplified. Then 16 S rRNA was subjected to molecular evolution analysis. Results: The bacteria were identified by both biochemical and molecular characterization and confirmed as Vibrio cholerae SPAB1, SPAB4, and SPAB5 (with NCBI Gene Bank Accession No: KT985959.1, KT985960.1, and KT985961.1, respectively). The bacteria were confirmed by 16S r RNA sequencing which shows a high degree of homology with the existing sequence and a comparison was carried out with amplified 16S rRNA gene sequence and NCBI sequence database. Molecular analysis of 16S rRNA generated an evolutionary and phylogenetic tree with a maximum identity of 95-99%. Conclusion: The three strains were new: KT985959.1, KT985960.1, and KT985961.1 are deposited in the NCBI database for future case studies. The strains were cardinal in designing the targeted drug.
Keywords: 16S rRNA; KT985959.1; KT985960.1; KT985961.1.; Vibrio cholerae